Pathophysiology and pharmacological management of pulmonary and cardiovascular features of COVID-19. (April 2021) - Hamouche, Walid; Bisserier, Malik; Brojakowska, Agnieszka; Eskandari, Abrisham; Fish, Kenneth; Goukassian, David A.; Hadri, Lahouaria
Abstract: The first confirmed case of novel Coronavirus Disease 2019 (COVID-19) in the United States was reported on January 20, 2020. As of November 24, 2020, close to 12.2 million cases of COVID-19 was confirmed in the US, with over 255, 958 deaths. The rapid transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), its unusual and divergent presentation has strengthened the status of COVID-19 as a major public health threat. In this review, we aim to 1- discuss the epidemiological data from various COVID-19 patient cohorts around the world and the USA as well the associated risk factors; 2- summarize the pathophysiology of SARS-CoV-2 infection and the underlying molecular mechanisms for the respiratory and cardiovascular manifestations; 3- highlight the potential treatments and vaccines as well as current clinical trials for COVID-19. Graphical abstract: Unlabelled Image Highlights: COVID-19 represents a great threat to people's health worldwide with a high transmission rate and socioeconomic impacts. Respiratory and cardiovascular conditions showed higher risks of complications and mortality of COVID-19 patients Efficacy and safety of investigational drugs and other potential treatments for COVID-19.